Estandarización de los procesos de producción de leche de ganado vacuno, en la granja UDLA Nono mediante la aplicación de herramientas de mejora para incrementar la productividad y la calidad del producto - Guanangui Guamán, Vanessa Valeria (2016)
This degree project is located along its chapters describes the situation of academic project farm UDLA, specifically focused on livestock management for milk production. As an introduction it presents generalities, organizational characteristics and the academic commitment of the Udla farm for students. Below we describe the concepts and the panorama to provide general support to the reader against the survey and documentation of the initial situation of the State of farm UDLA. The proposal for standardization in milk production processes are based on good practices livestock for dairy production of the Ecuador Guide; It is the starting point for the academic project is planned to achieve the aforementioned guide certification; making improvements in the standard of living of the workers of the farm, the welfare of livestock and milk production quality.